Inspiring middle and secondary learners honoring differences and creating community through differentiating instructional practices - Kryza, Kathleen; Stephens, S. Joy.; Duncan, Alicia; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2007)
The authors present a strong foundation with examples and ideas for creating an engaging classroom environment and building a community of learners who honour themselves and each other. Readers are guided step-by-step through the process of gathering student data, and show how to use this data to inform instructional practice.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Differentiated teaching staffs; Middle school education; Education, Secondary; Differentiation (Developmental psychology); Electronic books